A new generation of real-time simulation techniques - Quesada, C.; Alfaro, I.; González, D.; Cueto, E. (Jornada de Jóvenes Investigadores del I3A, 2014)
This work presents a novel methodology for the development of real-time simulation techniques. They are focused on the PGD method, which allows the solution of complex problems by pre-calculating all the possible results. Subsequently, applications efficiently process these data to show particular results on demand.